Twister - Hunt, Helen, 1963-; Paxton, Bill.; Bont, Jan de.; Warner Home Video (Firm); Universal Pictures (Firm); Warner Bros. Pictures (Burbank, CA : Warner Home Video, 1997)
Helen Hunt and Bill Paxton play scientists pursuing the most destructive weatherfront to sweep through mid- America's Tornado Alley in 50 years.
Rated PG-13.
For specific features see interactive menu.
Closed-captioned for the hearing impaired.
"Rated PG-13 for intense depiction of very bad weather"-- container.
Directed by Jan De Bont ; written by Michael Crichton & Anne-Marie Martin.
Helen Hunt, Bill Paxton.
Keywords: Films for the hearing impaired; Tornadoes -- Drama -- Video recordings; Feature films